Factors influencing quality of life in patients followed in the neurosonology laboratory for carotid stenosis - Fadrná, Táňa; Mikšová, Zdeňka; Herzig, Roman; Langová, Kateřina; Ličman, Libor; Školoudík, David (Health and quality of life outcomes, 2018)
BACKGROUND: Quality of life (QoL) is one of the main endpoints in stroke prevention or acute stroke treatment studies. The aim of the current study was to identify risk factors affecting the QoL of patients with carotid stenosis in stroke prevention. METHODS: Self-sufficient patients (50-80 years of age) with ≥20% carotid artery stenosis followed in the neurosonology laboratory, and without any severe illnesses within the last 12 months, dementia, or psychiatric disorders were selected for the study after signing informed consent. Patients completed two standardized QoL questionnaires (WHOQoL-BREF and EQ-5D-3 L) and a visual pain scale, provided covariate variables (medication, age, gender, education, and social situation), and the blood pressure and body mass indexes were recorded. Logistic regression (forward stepwise method) was used to identify factors affecting the individual domains of QoL questionnaires. RESULTS: Of the 584 consecutive patients, 502 met the inclusion criteria and 344 completely filled both QoL questionnaires (164 men; mean age, 69.7 ± 7.8 years). An independent predictor of worse QoL in all domains was pain. Independent factors decreasing the QoL were lower level of education and blood pressure in the physical health domain, female gender in the psychological domain, and male gender in the social relationships domain. Independent factors decreasing satisfaction with health status were female gender and higher blood pressure. Factors negatively influencing the satisfaction with the QoL were living alone, lower level of education, and higher diastolic blood pressure (WHOQoL-BREF). Factors negatively influencing mobility were age, male gender, living alone, lower level of education, and higher body mass index (EQ-5D-3 L; p < 0.05 in all cases). CONCLUSIONS: Pain, blood pressure, body mass index, education, living alone, gender, and age were associated with the QoL in patients with carotid stenosis. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02360137 . Registered on 26 January 2015.
Keywords: logistické modely; průzkumy a dotazníky; Female; Pain Measurement; Age Factors; Quality of Life; Risk factors; ženské pohlaví; Logistic Models; Surveys and Questionnaires; cévní mozková příhoda; kvalita života; věkové faktory; lidé; Stroke; měření bolesti; bolest; ultrasonografie dopplerovská transkraniální; Risk Factors; Sex Factors; Male; Carotid Stenosis; Quality of life; Aged; sexuální faktory; stenóza arteria carotis; Ultrasonography, Doppler, Transcranial; rizikové faktory; Pain; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Questionnaire; Humans